1983
DOI: 10.2135/cropsci1983.0011183x002300030033x
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of Male‐Sterile T‐Cytoplasm Maize to Male Fertility in Tissue Culture1

Abstract: This study was conducted to determine the inheritance of altered traits in plants regenerated from Texas male‐sterile cytoplasm (T) maize (Zea mays L.) tissue cultures. Plants were regenerated from AlSSTcms (rf1rf1;Rf2Rf2) tissue cultures grown on control media or on media containing different levels of streptomycin. Of 169 regenerated plants, eight expressed unexpected changes to male fertility and/or resistance to Helminthosporium maydis pathotoxin even though the cultures had not been selected for pathotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…The maize urf13 gene is located upstream of a conserved mitochondrial gene termed orf221, which encodes a membranebound protein (Prioli et al, 1993), now identified as ATP4 (Heazlewood et al, 2003). Critical confirmation that urf13 causes pollen disruption came from characterizing mitochondrial genomes in fertile revertants that arose from cell culture (Gengenbach et al, 1981), in which were detected deletions that disrupted the urf13 gene (Umbeck and Gengenbach, 1983;Abbott and Fauron, 1986;Rottmann et al, 1987). A particularly important revertant was described by Wise et al (1987), who observed that a 5-bp insertion in urf13, causing a frame shift and a premature stop codon, was sufficient to confer fertility.…”
Section: Complex Mitochondrial Loci Associated With Cms the Multiply mentioning
confidence: 99%
“…The maize urf13 gene is located upstream of a conserved mitochondrial gene termed orf221, which encodes a membranebound protein (Prioli et al, 1993), now identified as ATP4 (Heazlewood et al, 2003). Critical confirmation that urf13 causes pollen disruption came from characterizing mitochondrial genomes in fertile revertants that arose from cell culture (Gengenbach et al, 1981), in which were detected deletions that disrupted the urf13 gene (Umbeck and Gengenbach, 1983;Abbott and Fauron, 1986;Rottmann et al, 1987). A particularly important revertant was described by Wise et al (1987), who observed that a 5-bp insertion in urf13, causing a frame shift and a premature stop codon, was sufficient to confer fertility.…”
Section: Complex Mitochondrial Loci Associated With Cms the Multiply mentioning
confidence: 99%
“…Toxin-resistant mutants were also obtained from tissue cultures without T-toxin selection. All of these plants were also male fertile (Brettell et al, 1980;Umbeck and Gengenbach, 1983). Because all of the tissue-culture derived mutants resulted in the coordinate change in phenotype from toxin sensitivity to insensitivity and male sterility to male fertility, it was suggested that these two traits were controlled by the same or tightly linked mitochondrial genes (Gengenbach et al, 198 1;Kemble et al, 1982;Umbeck and Gengenbach, 1983).…”
Section: Disease Susceptibility and Male Sterilitymentioning
confidence: 99%
“…Concurrently, a map-based approach took advantage of the male-fertile, toxin-insensitive mutants described above. In 19 of 20 such mutants, a 6.7-kb XhoI mitochondrial DNA restriction fragment was altered due to a partial deletion (Gengenbach et al, 1981;Kemble et al, 1982;Umbeck and Gengenbach, 1983;Fauron et al, 1987). The remaining male-fertile mutant, T-4, retained the 6.7-kb XhoI fragment.…”
Section: Disease Susceptibility and Male Sterilitymentioning
confidence: 99%
“…It would be interesting to establish whether tllis effect of ploidy results from the greater tolerance of polyploid genotypes to chromosome aberrations or whether the cell cycles arc less easy to control in vitro for the larger gcnomes of the polyploids. It is interesting that differences in stability were observed between species of the same ploidy (35).…”
Section: Mechanisms Associated With Errors In Cell Division In Vitromentioning
confidence: 99%
“…In some cases these appear to involve changes in the proportions ofmt DNA circular molecules of different size (29) whilst in other cases structural alteration, such as inversions and duplications, in tl1c main mt DNA genome arc invoked ( 15). Tissue culture-induced changes in the mt DNA genome associated with cytoplasmic male sterility are well known (35) but more recently it appears that changes in mitochondrial genome organisation can also he related to embryogenic potential. In wheat, a specific region of the mt DNA genome is absent in cells which are non-embryogenic and certain DNA fragments are amplified in embryogenic cells (15,16).…”
Section: Mechanisms Of Molecular Variation In Plant Tissue Culturementioning
confidence: 99%